Micro-Evidence on Product and Labor Market Regime Differences between Chile and France - Sabien Dobbelaere; Rodolfo Lauterbach; Jacques Mairesse (Institute for the Study of Labor (IZA), 2015)
Institutions, social norms and the nature of industrial relations vary greatly between Latin American and Western European countries. Such institutional and organizational differences might shape firms' operational environment in general and the type of competition in product and labor markets in particular. Contributing to the literature on estimating simultaneously product and labor market imperfections, this paper quantifies industry differences in both types of imperfections using firm-level data in Chile a non-OECD member under the considered time period and France. We rely on two extensions of Hall's econometric framework for estimating price-cost margins by nesting three labor market settings (perfect competition or right-to-manage bargaining, efficient bargaining and monopsony). Using an unbalanced panel of 1,737 firms over the period 1996-2003 in Chile containing unique data on firm-level output price indices and 14,270 firms over the period 1994-2001 in France, we first classify 20 comparable manufacturing industries in 6 distinct regimes that differ in the type of competition prevailing in product and labor markets. We then investigate industry differences in the estimated product and labor market imperfections. Consistent with differences in institutions and in the industrial relations system in the two countries, we find important regime differences across the two countries. In addition, we observe cross-country differences in the levels of product and labor market imperfections within regimes.
Keywords: C23; D21; J51; L13; 330; rent sharing; monopsony; price-cost mark-ups; production function; panel data